Cultural determinants of research community participation - Rahim R.E.A.; Ali N.; Jais J. (IEEE Computer Society, 2023)
Computer supported cooperative work; Information management; Information systems; Knowledge management; Management science; Metadata; Societies and institutions; Community; Cultural determinants; Higher education; Higher education institutions; Malaysia; Organizational learning; Research communities; Top management support; Education